Arsenic in groundwater of West Bengal: Implications from a field study - Neidhardt, Harald (Karlsruher mineralogische und geochemische Hefte : Schriftenreihe des Instituts für Mineralogie und Geochemie, 2012)
This publication presents results of an interdisciplinary field study assessing the contribution of biological and inorganic processes in the mobilisation and accumulation of arsenic in groundwater of the Bengal Delta Plain, West Bengal. Investigations were focussed on the distribution of arsenic in sediments and shallow groundwater of two representative study sites. All results were combined in an effort to develop a conceptional model describing the mobility of arsenic in West Bengal aquifers.